Eksplorasi Motif Geblek Renteng: Aplikasi Grup Kristalografi dengan Graphical User Interface (GUI) - Putranto, Sumbaji; Ratnasari, Gamarina Isti; Purnama, Pratama Wahyu (Pusat Studi Pengembangan Pembelajaran Matematika Sekolah UIN Sunan Kalijaga Yogyakarta Jl. Marsda Adisucipto, Yogyakarta 55281, 2023)
Geblek is one of Kulon Progo's specialty foods made from cassava flour with a shape resembling a figure eight. Geblek is the main pattern used in the batik typical of Kulon Progo. The batik motif uses repetitive and symmetrical patterns. The application of mathematics, especially cryptography, can be used to find repetitive patterns that can inspire batik motifs. This research aims to describe how a basic geblek pattern from Kulon Progo can be transformed into various other patterns using the concept of plane crystallography. The geblek pattern is applied to 17 crystallographic groups, resulting in 17 batik motifs. The use of Graphical User Interface (GUI) in MATLAB will make it easier to form batik motifs. Based on the exploration results, 17 patterns were derived from the basic pattern of Kuln Progo geblek. Uniquely, from these 17 patterns, there are the same and similar patterns. In other words, the patterns found from the basic geblek pattern do not reach 17 patterns. The development pattern of Kulon Progo geblek is further described in this article.